Thermal versus mechanical topography: an experimental investigation in a rotating baroclinic annulus - Marshall, SD; Read, PL (Taylor and Francis, 2020)
We present a series of experimental investigations in which a differentially-heated annulus was used to investigate the effects of topography on rotating, stratified flows. In particular, we investigate blocking effects via azimuthally varying differential-heating and compare them to previous experiments utilising partial mechanical barriers. The thermal topography used consisted of a flat patch of heating elements covering a small azimuthal extent of the base, forming an equivalent of a partial barrier, to study the difference between blocked and unblocked flow. These azimuthally-varying heating experiments produced results with many similarities to our previous experiments with a mechanical barrier, despite the lack of a physical obstacle or formation of bottom-trapped waves. In particular, a unique flow structure was found when the drifting flow and the topography interacted in the form of an “interference” regime at low Taylor number, but forming an erratic “irregular” regime at higher Taylor number. This suggests that blocking may be induced by either or both of a thermal or mechanical inhomogeneity. Evidence of coherent/persistent resonant wave triads was noted in both kinds of experiment, though the component wavenumbers of the wave-triads and their impact on the flow was found to depend on the topography in question.